Recensions / Book Reviews: CONSTAS DIMITRI AND STAVROU THEOFANIS G., Editors, Greece Prepares for the Twenty-first Century - Evriviades, Marios (Études helléniques / Hellenic Studies, 2015)
CONSTAS DIMITRI AND STAVROU THEOFANIS G., Editors, Greece Prepares for the Twenty-first Century Washington, D.C.: The Woodrow Wilson Center Press and Baltimore and London: the Johns Hopkins University Press, 1995 (Published in cooperation with the lnstitute of International Relations, Panteion University). XI + 319 p.